Caracterização epidemiológica das arboviroses e sua correlação com a densidade populacional de vetores - Chaves, Tatiany Liberal Dias (2019)
The occurrence of Aedes aegypti and Aedes albopictus is observed all over the world. In Brazil, they were introduced in the late nineteenth century, and because of the good adaptation to the climate and different types of breeding places, they quickly obtained a wide distribution throughout the country. The differences between them are determinant for the dynamics of arbovirus transmission, virus propagation and species spread. In view of the large number of cases related to the presence of Aedes, this work covers the hypothesis that socioenvironmental and climatic factors may interfere in the vector population, increase in the number of A. aegypti and A. albopictus breeding sites, and consequently increase the incidence of arboviruses. This study aimed to characterize the epidemiology of arboviruses in the municipality of João Pessoa / PB and its correlation with the population density of vectors and climatic factors in the period from 2015 to 2017, through the analysis of documentary data. An Infestation Index Survey was carried out in two distinct strata and correlated with data on climatic and socioenvironmental factors. The epidemiological data of stratum I showed a higher number of arboviruses (Dengue, Zica, Chikungunya) reported, with a significant difference (p = 0.001) in relation to Stratum II. The correlation data between the number of cases of arbovises reported with the House Infestation Index, presented suggest a moderate correlation between the variables in Stratum II.